Applying the RE-AIM Framework for the Evaluation of a Clinical Decision Support Tool for Pediatric Head Trauma: A Mixed-Methods Study - Masterson Creber, Ruth M.; Dayan, Peter S.; Kuppermann, Nathan; Ballard, Dustin W.; Tzimenatos, Leah; Alessandrini, Evaline; Mistry, Rakesh D.; Hoffman, Jeffrey; Vinson, David R.; Bakken, Suzanne; for the Pediatric Emergency Care Applied Research Network (PECARN) and the Clinical Research on Emergency Services and Treatments (CREST) Network (Applied Clinical Informatics, 2018)
Background The overuse of cranial computed tomography (CT) to diagnose potential traumatic brain injuries (TBIs) exposes children with minor blunt head trauma to unnecessary ionizing radiation. The Pediatric Emergency Care Applied Research Network and the Clinical Research on Emergency Services and Treatments Network implemented TBI prediction rules via electronic health record (EHR) clinical decision support (CDS) to decrease use of CTs in children with minor blunt head trauma.Objective This article aims to facilitate implementation and dissemination of a CDS alert into emergency departments around the country.Methods We evaluated the EHR CT CDS tool through a mixed-methods analysis of 38 audio-recorded interviews with health care stakeholders and quantitative data sources, using the Reach, Efficacy, Adoption, Implementation, and Maintenance framework.Results Reach—The demographics of participants enrolled in the clinical trial were consistent with national estimates of TBI prevalence. Efficacy—There was a variable and modest reduction in CT rates for the 8,067 children with minor head trauma whose clinicians received CDS. Adoption—The EHR CT CDS tool was well matched with the organizational mission, values, and priorities of the implementation sites. Implementation— The most important predisposing factors for successful implementation were the presence of an approachable clinical champion at each site and belief that the tool was a relevant, reusable knowledge asset. Enabling factors included an effective integration within the clinical workflow, organizational investment in user training, and ease of use. Maintenance— Reinforcing factors for the EHR CT CDS tool included a close fit with the institutional culture, belief that it was useful for providers and families, and a good educational and informational tool. As such, the EHR CT CDS tool was maintained in clinical practice long after study completion.Conclusion Data from this mixed-methods study complement findings from the efficacy trial and provide critical components for consideration prior to integration and subsequent dissemination of the EHR CT CDS tool.Trial Registration NCT01453621, Registered September 27, 2011
Keywords: clinical decision support; clinical trial; blunt head trauma; traumatic brain injury; implementation; child